Price, Discounting and Differentials in the Tourism Industry: A Study on Kerala Tourism - James, Gracious (Indian Journal of Finance, 2012)
There is widely accepted evidence that prices are one of the most important factors in travel planning. In the tourism industry, the price elasticity of demand or sensitivity to changes in price need to be considered, because travel is not an essential activity and many alternatives for leisure time are available. Discount for last minute sales have been used extensively by tour operators due to the highly perishable nature of the product. Demand for tourism products is the relationship between the amount of the service that customers will buy and the price fixed for the service. Several factors impinge in different ways on tourism price competitiveness. Discounted prices are commonly applied in the off-season. Although it can be useful in gaining immediate business, discounting does not usually differentiate a product from the competition and is generally quickly matched by competitors. The aims of this paper are: first, to demonstrate the importance of price, discounts and differentials in travel decisions; second, to analyze the 'discounting methods' of different tourism units in Kerala.